2021
DOI: 10.48550/arxiv.2107.09383
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Stability of cycles in a game of Rock-Scissors-Paper-Lizard-Spock

Abstract: We study a system of ordinary differential equations in R 5 that is used as a model both in population dynamics and in game theory, and is known to exhibit a heteroclinic network formed by three types of elementary heteroclinic cycles. We show the asymptotic stability of the network for parameter values in a range compatible with the two interpretations of the equations. We obtain estimates of the relative attractiveness of each one of the cycles by computing their stability indices. For the parameter values e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
1
0
0
Order By: Relevance
“…We have done these calculations numerically, and found that except for the A sequences, all sequences have a 'cusp' shaped local basin -that is, one in which the measure decreases to zero as the network is approached. These numerical calculations are supported by analytical calculations in [64], for the A, B and AAB cycle. However, these sequences are not hard to find by randomly selecting initial conditions for numerical integrations, which seems somewhat counter-intuitive.…”
Section: Discussionsupporting
confidence: 53%
“…We have done these calculations numerically, and found that except for the A sequences, all sequences have a 'cusp' shaped local basin -that is, one in which the measure decreases to zero as the network is approached. These numerical calculations are supported by analytical calculations in [64], for the A, B and AAB cycle. However, these sequences are not hard to find by randomly selecting initial conditions for numerical integrations, which seems somewhat counter-intuitive.…”
Section: Discussionsupporting
confidence: 53%